Deposition of Zinc Sulfide Thin Films From Zinc(II) Thiosemicarbazones as Single Molecular Precursors Using Aerosol Assisted Chemical Vapor Deposition Technique - Palve, Anil M. (Frontiers in Materials, 2019)
ZnS thin films have been deposited on a glass substrate by aerosol assisted chemical vapor deposition (AACVD) from the Zinc thiosemicarbazone precursors is reported. This approach exploits the use of Zn(II) thiosemicarbazone complexes as single source precursors. Thiosemicarbazone complexes such as Zn(cinnamtscz)2, Zn(4-Clbenztscz)2, ZnCl2(cinnamtsczH)2, ZnCl2(4-ClbenztsczH)2 and ZnCl2(thioptsczH)2 (Where, cinnamtsczH = cinnamaldehyde, 4-ClbenztsczH = 4-chlorobenzaldehyde and thioptsczH = thiophene 2-carboxaldehyde thiosemicarbazones) were used as single source precursors for the deposition of thin films. They were obtained by treatment of zinc chloride with various thiosemicarbazone as sulfur containing ligands. The deposition was carried out in the temperature range between 400 to 500 °C on a glass substrate. The X-ray diffraction pattern revels the hexagonal phase of ZnS thin films. Scanning electron microscopy and atomic force microscopy analysis shows granular shaped type of surface texture. The energy dispersive X-ray analysis indicates 1:1 stoichiometry of zinc and sulfur. UV-Visible spectroscopy is used to find the optical band gaps of thin films using Tauc’s plots.